Nuclear DNA replicates during zygote development in Arabidopsis and Torenia fournieri. Issue 1 (18th November 2020) - Liu, Xue-Qiong; Shi, Jiao-Jiao; Fan, Hua; Jiao, Jiao; Gao, Long; Tan, Li; Nagawa, Shingo; Wang, Dan-Yang
Abstract: The progression of the cell cycle is continuous in most cells, but gametes (sperm and egg cells) exhibit an arrest of the cell cycle to await fertilization to form a zygote, which then continues through the subsequent phases to complete cell division. The phase in which gametes of flowering plants arrest has been a matter of debate, since different phases have been reported for the gametes of different species. In this study, we reassessed the phase of cell-cycle arrest in the gametes of two species, Arabidopsis ( Arabidopsis thaliana ) and Torenia fournieri . We first showed that 4', 6-diamidino-2-phenylindole staining was not feasible to detect changes in gametic nuclear DNA in T. fournieri . Next, using 5-ethynyl-2'-deoxyuridine (EdU) staining that detects DNA replication by labeling the EdU absorbed by deoxyribonucleic acid, we found that the replication of nuclear DNA did not occur during gamete development but during zygote development, revealing that the gametes of these species have a haploid nuclear DNA content before fertilization. We thus propose that gametes in the G1 phase participate in the fertilization event in Arabidopsis and T. fournieri . Abstract : The replication of nuclear DNA does not occur during gamete development but during zygote development.